Effects of bortezomib on HIF-1 and HIF-2 transcriptional activities - Abd Aziz, Noraini (2013)
Bortezomib is the first proteasomal inhibitor (PI) to be used therapeutically in humans for treating relapse cases of multiple myeloma and mantle cell lymphoma. A proposed mechanism is that it prevents proteasomal degradation of pro-apoptotic proteins, leading to enhance apoptosis. Although the alpha subunit of hypoxia inducible factor 1 (HIF-1) is not degraded, the heterodimeric HIF-1 fails to transactivate target genes. HIF-1 and HIF-2 are related hypoxia-inducible transcription factors that are important for survival of hypoxic tumor cells. Most reports have focused on the effects of bortezomib on HIF-1 but not HIF-2 transcriptional activities. In the present study, the effect of bortezomib on HIF-2 activity in cells with different levels of expression of the HIF-1α and HIF-2α subunits, was investigated. Results showed that bortezomib treatment suppressed the transcription and expression of CA9, a HIF-1-specific target gene, but had minimal effects on EPO and GLUT-1, which are the target genes of both HIF-1 and HIF-2. A similar dichotomy of responses was also seen with exogenously-introduced hypoxia response elements of CA9 and EPO. These data led to a conclusion that bortezomib attenuates the transcriptional activity of only HIF-1 but not HIF-2. This novel finding on the lack of inhibitory effect of bortezomib on HIF-2 transcriptional activity will be important in the improvement of design and treatment modalities to enhance the efficacy of this and other proteasomal inhibitor drugs.